ROS production by endogenously generated Protoporphyrin IX in murine leukemia cells - Diez, Berenice Andrea (2009)
Endogenous production of Protoporphyrin IX (Pp1X) is succesfully exploited for photodynamic therapy (PDT) on malignant cells, following 5-aminolevulinic acid (ALA) administration and light irradiation. This treatment kills cancer cells by damaging organelles and impairing metabolic pathways via cellular reactive oxygen species (ROS) generation. We studied the efficiency of Pp1X synthetized from ALA on ROS generation, in the vincristine resistant (LBR-V160), Doxorubicin resistant (LBR-D160) and sensitive (LBR-) murine leukemia cells. Cells were incubated 4hr with 1mM ALA and then irradiated during different times with flourescent light. One hour later, production of ROS was analyzed by flow cytometry using different flourescent probes: Hydroethidine (HE) for superoxide anion, 2,7 Dichlorodihydroflourescein diacetate (DCFH-DA) for hydrogen peroxide; mitochondrial damage was examined with 3,3 Dinexyloxacarbocyanine iodide (DIOC6). We found that superoxide anion production in the three cell lines increased with irradiation time whereas no peroxide hydrogen was detected. Mitochondrial damage also increased in an irradiation time dependent manner, being higher in the Vincristineresistant line. Previous studies have demonstrated that apoptotic cell death increased with irradiation time, which is consistent with these results, indicating that ROS are critical in ALA-PDT efficiency to kill malignant cells.